Peste des Petits Ruminants Virus Surveillance in Domestic Small Ruminants, Mozambique (2015 and 2017) - Mapaco, Lourenço; Monjane, Iolanda; Fafetine, José; Arone, Dercília; Caron, Alexandre; Chilundo, Abel; Quembo, Carlos; Carrilho, Maria Do Carmo; Nhabomba, Virginia; Zohari, Siamak; Achá, Sara (Frontiers in Veterinary Science, 2019)
Peste des Petits Ruminants (PPR), a transboundary animal disease affecting mainly goats and sheep is caused by a morbillivirus and threatens food security and livelihoods as morbidity and mortality rates can reach 90%. There are no records of PPR in Mozambique, but the disease situation in Tanzania and the ability of PPR virus to rapidly spread across countries constitute a high risk for the 4.1 millions of goats and sheep in Mozambique. A total of 4995 goats and sheep were sampled in several provinces during 2015 and 2017 to assess the status of PPR virus (PPRV) in Mozambique and to contribute to surveillance along the border with Tanzania. The sera were screened for anti-PPRV antibodies using a commercial PPR competition ELISA (c-ELISA) and the haemagglutinin based PPR blocking ELISA (HPPR-bELISA). The swabs were tested using one-step RT-PCR for detection of PPRV RNA. The overall percentage of animals with anti-PPRV antibodies by c-ELISA, was 0.46% [0.30 – 0.70]. However, all the sera positive on c-ELISA were confirmed to be negative by the HPPR-bELISA. Considering that all the swabs were negative for detection of PPRV, and neither clinical cases were observed during passive surveillance and active sampling, nor symptoms were reported, these results suggest that PPRV is not present in Mozambique.